2015
DOI: 10.1021/acscombsci.5b00117
|View full text |Cite
|
Sign up to set email alerts
|

Single-Tailed Lipidoids Enhance the Transfection Activity of Their Double-Tailed Counterparts

Abstract: Cationic lipid-like molecules (lipidoids) are widely used for in vitro and in vivo gene delivery. Nearly all lipidoids developed to date employ double-tail or multiple-tail structures for transfection. Single-tail lipidoids are seldom considered for transfection as they have low efficiency in gene delivery. So far, there is no detailed study on the contribution to transfection efficiency of single-tail lipidoids when combined with standard double-tail lipidoids. Here, we use combinatorial chemistry to synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Lipid-like molecules that are substituted with only one tail result in poor efficiency compared to their bi-tailed counterparts. However, a synergistic effect could be observed when mixing mono- and bi-tailed lipids at different ratios. , Monotailed lipids increase the surface charge, whereas bi-tailed lipids decrease lipid nanoparticle size and increase stability . In the field of lipidoid synthesis, attachment of more than two alkyl tails is considered to be very important to promote high gene delivery efficiencies. , …”
Section: Lipid-based Dna Delivery Systemsmentioning
confidence: 99%
“…Lipid-like molecules that are substituted with only one tail result in poor efficiency compared to their bi-tailed counterparts. However, a synergistic effect could be observed when mixing mono- and bi-tailed lipids at different ratios. , Monotailed lipids increase the surface charge, whereas bi-tailed lipids decrease lipid nanoparticle size and increase stability . In the field of lipidoid synthesis, attachment of more than two alkyl tails is considered to be very important to promote high gene delivery efficiencies. , …”
Section: Lipid-based Dna Delivery Systemsmentioning
confidence: 99%
“… 9 , 25 , 26 , 27 It has been reported that TE is highly correlated with nanoparticle size and surface charge, both of which are affected by lipid composition. 28 , 29 Additionally, the active targeting and appropriate characteristics of CLs can also be obtained by simply tailoring the lipid compositions, which are crucial to the outperformance of CLs in the body. Therefore, the rational design of CLs requires a full understanding of the relationship between lipid composition and therapeutic outcome.…”
Section: Main Textmentioning
confidence: 99%
“…By contrast, single-chained cationic lipids are more prone to form unstable lipoplexes characterized by higher cytotoxicity and reduced transfection efficiency (Lv et al, 2006;Pinnaduwage et al, 1989). Of note, the combination of single-and doubletailed lipids to give mixed liposomes had a positive synergistic effect on the transfection efficiency (Li et al, 2013;Wu et al, 2016).…”
Section: Aliphatic Chainsmentioning
confidence: 99%